English and Spanish oral cancer information on the Internet: a pilot surface quality and content evaluation of oral cancer Web sites - Irwin, Jeannie Y. (J Public Health Dent, 2011)
OBJECTIVE: Oral and pharyngeal cancers are responsible for over 7,600 deaths each year in the United States. Given the significance of the disease and the fact that many individuals increasingly rely on health information on the Internet, it is important that patients and others can access clear and accurate oral cancer information on the Web. The objective of this study was threefold: a) develop an initial method to evaluate surface and content quality of selected English- and Spanish-language oral cancer Web sites; b) conduct a pilot evaluation; and c) discuss implications of our findings for dental public health. METHODS: We developed a search strategy to find oral cancer sites frequented by the public using Medline Plus, Google, and Yahoo in English and Spanish. We adapted the Information Quality Tool (IQT) to perform a surface evaluation and developed a novel tool to evaluate site content for 24 sites each in English and Spanish. RESULTS: English-language sites had an average IQT score of 76.6 (out of 100) and an average content score of 52.1 (out of 100). Spanish-language sites had an average IQT score of 50.3 and an average content score of 25.6. CONCLUSIONS: The study produced a quality assessment of oral cancer Web sites useful for clinicians and patients. Sites provided more information on clinical presentation, and etiology, and risk factors, than other aspects of oral cancer. The surface and quality of Spanish-language sites was low, possibly putting Hispanic populations at a disadvantage regarding oral cancer information on the Web.